The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00464-014-3416-y
|View full text |Cite
|
Sign up to set email alerts
|

Single port/incision laparoscopic surgery compared with standard three-port laparoscopic surgery for appendicectomy: a randomized controlled trial

Abstract: Background and objectiveThe aim of this study was to compare the effectiveness of single port/incision laparoscopic surgery (SPILS) with standard three-port laparoscopic surgery for appendicectomy in adults. Feasibility data was collected to evaluate generalizability to other single-port techniques such as cholecystectomy.MethodsThis was a single-center, randomized controlled trial. Participants were randomized to receive either SPILS or standard three-port laparoscopic appendicectomy. The primary patient-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Nevertheless, SILA generally requires a higher level of technical expertise compared to laparoscopic appendectomy with multi-port because of the scarcity of instruments or the lack of triangulation. Furthermore, SILA is performed using a 5-mm laparoscope or specialized instruments such as the umbilical port 9. Additionally, several tens of thousands of dollars are needed in order to introduce a new laparoscope system.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, SILA generally requires a higher level of technical expertise compared to laparoscopic appendectomy with multi-port because of the scarcity of instruments or the lack of triangulation. Furthermore, SILA is performed using a 5-mm laparoscope or specialized instruments such as the umbilical port 9. Additionally, several tens of thousands of dollars are needed in order to introduce a new laparoscope system.…”
Section: Discussionmentioning
confidence: 99%
“…An early theoretical concern for single incision laparoscopic surgery was that reduced surgical access and visualization might compromise patient safety [ 15 ]. And early reports suggested that SILA might be associated with a higher incidence of wound infection [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…And early reports suggested that SILA might be associated with a higher incidence of wound infection [ 16 ]. However, as laparoscopic techniques and equipment have improved, recent studies have reported that SILA has similar postoperative complication rates to CLA [ 15 17 ]. In a review of randomized trials, Markar et al [ 5 ] found no significant difference between CLA and SILA not only in the overall incidence of surgical complications, but also in the incidence of wound infection, intra-abdominal collection, and ileus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations